Antimony-dependent expansion for the Keggin heteropolyniobate family. Issue 15 (19th January 2015) - Zhang, Zhe-Yu; Peng, Jun; Shi, Zhen-Yu; Zhou, Wan-Li; Khan, Shifa Ullah; Liu, Hong-Sheng
Abstract : Antimony-dependent syntheses leading to the expansion of the Keggin heteropolyoxoniobate family involved nine new members. Abstract : Nine new Sb-bicapped α-Keggin-type heteropolyoxoniobates (HPNb) were synthesized under hydrothermal conditions. Among them, the As-centered HPNb was never reported before, and the two dimer compounds are the biggest isolated HPNbs at present.